2021
DOI: 10.1001/jamanetworkopen.2021.24152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Buprenorphine Rotation in Patients Receiving Long-term Opioids for Chronic Pain

Abstract: IMPORTANCE Individuals with chronic pain who use long-term opioid therapy (LTOT) are at risk of opioid use disorder and other harmful outcomes. Rotation to buprenorphine may be considered, but the outcomes of such rotation in this population have not been systematically reviewed.OBJECTIVE To synthesize the evidence on rotation to buprenorphine from full μ-opioid receptor agonists among individuals with chronic pain who were receiving LTOT, including the outcomes of precipitated opioid withdrawal, pain intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 103 publications
(733 reference statements)
0
12
0
Order By: Relevance
“… 182 For patients at increased risks when tapering because of complex persistent opioid dependence, transition to buprenorphine should be considered, although the evidence for this approach, like others, remains limited. 23 227 Multidisciplinary pain management programmes are probably effective at helping to reduce opioid dose. However, access remains an issue for people who are unable to take time off work, in regional areas where services are limited, and for people from culturally and linguistically diverse communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 182 For patients at increased risks when tapering because of complex persistent opioid dependence, transition to buprenorphine should be considered, although the evidence for this approach, like others, remains limited. 23 227 Multidisciplinary pain management programmes are probably effective at helping to reduce opioid dose. However, access remains an issue for people who are unable to take time off work, in regional areas where services are limited, and for people from culturally and linguistically diverse communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have considered the outcomes of clinical interventions to facilitate opioid tapering, including one Cochrane review and nine other systematic, scoping, and rapid reviews. 15 16 17 18 19 20 21 22 23 24 25 Included studies evaluate, among other things, pain management programmes, the drug management of withdrawal symptoms, and biomedical procedures. The variety of approaches to opioid tapering reflects the complexity of this process, the differing causes of chronic pain and approaches to treatment (biomedical, biopsychosocial, alternative medicine), and the presence of comorbidities such as substance use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Brand changes and switching to a generic equivalent opioid with an inappropriate tapering of the new “equivalent” opioid might result in inadequate analgesia, especially in individuals with chronic pain who use long-term opioid therapy (LTOT) [ 78 ]. Furthermore, the chronic use of opioids can lead to the development of tolerance and dependence, with consequent further narrowing of the drug’s therapeutic index and increased risk of side effects [ 69 ].…”
Section: Drugs With Narrow Therapeutic Index: Bioequivalence Versus T...mentioning
confidence: 99%
“…Buprenorphine rotation is a promising new strategy that can be used instead of tapering longterm opioid therapy (ltOt). A systematic review conducted by Powell et al [66], including 22 studies, showed that buprenorphine therapy reduced chronic pain intensity without precipitating opioid withdrawal symptoms. A novel strategy for starting buprenorphine and naloxone has been described in a critically ill intubated patient with an opioid use disorder using a rapid micro-induction (microdosing) technique.…”
Section: The Role Of the Intensivist In Combating The Opioid Epidemicmentioning
confidence: 99%